PERAN MOTIVASI, SELF EFFICACY, TRI PUSAT PENDIDIKAN, DAN EFEKTIVITAS PELATIHAN BREVET PAJAK DALAM MINAT BERKARIR MAHASISWA AKUNTANSI DIBIDANG PERPAJAKAN - Sri Lestari Yuli Prastyatini; Uum Helmina Chaerunisak; Rifah Ayu Wafiroh (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
This research is motivated by the phenomenon of a lack of student interest in a career in taxation, while the Indonesian government requires graduate students who have a career interest in taxation and graduates who are competent in the field of taxation. This study aims to determine the effect of motivation, self-efficacy, three educational centers, and the effectiveness of tax brevet training on the career interest of accounting students in the field of taxation partially or simultaneously. This research method uses a quantitative descriptive method and primary data using a questionnaire. The sampling technique used purposive sampling technique. This study used a sample of private university students in the city of Yogyakarta. This research managed to collect 150 respondents. The tool for processing data uses IBM SPSS version 20. The results of this study indicate that both simultaneously and partially motivation, self-efficacy, tri education centers and the effectiveness of tax brevet training affect the career interest of accounting students in the field of taxation by 74.2%, while the rest is 25.8% is influenced by other factors outside the variables of this study.